TMOD-07. ADVANCED ULTRA-HIGH FIELD MRI ON TUMOR HABITAT IN ORTHOTOPIC MOUSE MODELS FOR PEDIATRIC BRAIN TUMORS. (23rd April 2019) - Steiner, Jenna; Pierce, Angela; Griesinger, Andrea; Veo, Bethany; Knox, Aaron; Dahl, Nathan; Green, Adam; Foreman, Nicholas; Vibhakar, Rajeev; Serkova, Natalie
Abstract: Brain tumors are the second most common malignancy in childhood. Magnetic resonance imaging (MRI) is the preferred clinical modality for the management of pediatric brain tumors due to its exquisite soft tissue contrast and non-ionizing radiation. Pediatric brain tumors have a diverse array of clinical manifestations, cellular and molecular phenotypes, and tumor habitats. There is an unmet need to develop human-faithful pediatric mouse models and fast high-resolution functional MRI to characterize biologically relevant structure-function relationships in vivo . Here, we report on non-gadolinium, Multiparametric Advanced Fast Imaging (MAFI) at a 9.4T MRI scanner, followed by radiomics analysis to detect, characterize and differentiate three distinct brain tumor subtypes of orthotopic patient-derived xenograft (PDX) mouse models. The total MAFI scan time (turboRARE T2-MRI, FLAIR, intrinsic susceptibility (IS)-MRI, and diffusion weighted imaging (DWI)) was 17 minutes. High-resolution T2-MRI detected lesions (> 0.2 mm 3 ) in the posterior fossa for medulloblastomas, in the pons for DIPG, and in the cerebellum for ependymomas, with metastatic spread to cortex (medulloblastoma), spine (DIPG) and olfactory bulb (ependymoma), each n=12. IS-MRI revealed increased tumor blood volume (mostly in medulloblastomas) at the early stage of tumor engraftment. High cellularity (indicated by low ADC on DWI) was characteristic of medulloblastomas and ependymomas, along with high peritumoral edema on DWI and FLAIR. For radiomics analysis, each image was segmented into three regions (with 360 radiomics features each): well-defined tumor, peritumoral edema and tumor necrosis. A subset of twelve tumoral, six peritumoral and two necrotic MAFI radiomics features was found to be predictive of the tumor subtype (P<0.0002) independent of tumor anatomical location. In summary, the 9.4 Tesla MAFI MRI protocol discriminates among specific radiological features for three distinct orthotopic models: medulloblastomas exhibit higher levels of necrosis, cellularity and angiogenesis as compared to ependymomas (high peritumoral edema) and DIPG (low blood volume/vessel density).